EFL STUDENTS’ WTC EXPERIENCES THROUGH PROJECT-BASED LEARNING: A THEMATIC ANALYSIS - Lubis, Nazriani; Lubis, Asnarni; Delila, Eisya; Wardana, Andri (UIN Sumatera Utara, 2024)
EFL students are highly demanded both to engage and to involve intensively in classroom interaction in order to massively practice communication skill in English. In this case, EFL students can supportively participate in Willingness to Communicate (WTC) through the implementation of project-based learning. Given to this recent attention, this research investigates students’ WTC experiences during project completion. Qualitative research method with thematic analysis approach was applied and four eligible participants with specific criteria were chosen to answer the semi-structure interview. The emerging data were classified to importing two themes; conversational setting and particular interlocutors. Results reveal students’ higher WTC only occurred at the classroom under the lecturer’s surveillance, they tend to discuss with Bahasa during completing project outside the classroom. It implies that the implementation of project-based learning only offers situation-based activity to create the dynamic interaction among EFL students. The more systematic stages of project-based learning need to develop to promote higher WTC in EFL context.